Dampak Program CSR Binaan PT Pertamina RU II Sungai Pakning: Analisis Social Return on Investment (SROI) dan Sensitivitas - Nurhazana Nurhazana; Muhammad Luthfi iznillah; Sahat Roy Pianto (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
The purpose of this study is to see the impact of the CSR program of PT Pertamina RU II Sei Pakning through the analysis of Social Return on Investment and sensitivity. This research is descriptive quantitative by utilizing primary and secondary data. Primary data consists of data obtained from processing observational data and secondary data obtained from various literature sources. Based on the results of the SROI calculations for the four programs, it can be concluded that the social investment made for each program is feasible because all programs have a positive SROI score (more than 1) during the program implementation plan. In accordance with the results of the SROI calculation analysis, four programs from PT Pertamina RU II Sungai Pakning have generated benefits that are greater than the program costs. However, there are still opportunities to increase and expand the scope of benefits from the four programs.